KEANEKARAGAMAN DAN KEGUNAAN TUMBUHAN BAWAH PADA BEBERAPA TEGAKAN DI ARBORETUM BALAI PENELITIAN DAN PENGEMBANGAN TEKNOLOGI SERAT TANAMAN HUTAN (BP2TSTH) KUOK - Budi Siswanto, Arifin; Hadinoto, Hadinoto; Azwin, Azwin (Wahana Forestra: Jurnal Kehutanan, 2021)
Underground plants have an important role in soil and air conservation efforts, namely as a source of organic matter, preventing erosion, a source of germplasm and increasing air infiltration into the soil. This study aims to identify the types, diversity and use of understorey under stands of meranti, gaharu and mixed stands in the arboretum of the Kuok Forest Plant Fiber Technology Research and Development Institute (BP2TSTH). The data collection method used systematic sampling with a random start, with a sampling intensity of 5%. The number of plots observed for meranti, gaharu and mixed stands were 50, 25 and 25, respectively, with a plot size of 2 x 2 (m). In the stands were found 17 families of undergrowth consisting of 23 species and 10,338 individuals. In the agarwood stands there are 10 families of undergrowth consisting of 13 species and 9,696 individuals. In the agarwood stands there are 11 families with a diversity of 13 species and 10,328 individuals. Diversity Index and Evenness Index in meranti, gaharu and mixed stands respectively; 1.25 and 0.4; 0.72 and 0.28; 0.72 and 0.28. Paspalum conjugatum is a understorey species with the highest Importance Value Index (IVI) in the three stands.